Assessing the hazards from a BLEVE and minimizing its impacts using the inherent safety concept - Shariff, A.M. (Elsevier Ltd, 2016)
Many worlds' major process industry accidents are due to BLEVE such as at Feyzin, France, 1966 and San Juan Ixhuatepec, Mexico City, 1984. One of the approaches to eliminate or minimize such accidents is by the implementation of inherently safer design concept. This concept is best implemented where the consequence of BLEVE can be evaluated at the preliminary design stage, and necessary design improvements can be done as early as possible. Thus, the accident could be avoided or minimized to as low as reasonably practicable (ALARP) without resorting to a costly protective system. However, the inherent safety concept is not easy to implement at the preliminary design stage due to lack of systematic technique for practical application. To overcome these hurdles, this paper presents a new approach to assess process plant for the potential BLEVE at the preliminary design stage and to allow modifications using inherent safety principles in order to avoid or minimize major accidents. A model known as Inherent Fire Consequence Estimation Tool (IFCET) is developed in MS Excel spreadsheet to evaluate BLEVE impacts based on overpressure, radiation heat flux and missile effects. In this study, BLEVE impacts are the criteria used as the decision-making for the acceptability of the design. IFCET is integrated with iCON process design simulator for ease of data transfer and quick assessment of potential BLEVE during the design simulation stage. A case study was conducted to assess of potential BLEVE from a propane storage vessel at the design simulation stage using this new approach. The finding shows promising results that this approach has a potential to be developed as a practical tool. Â© 2016 Elsevier Ltd.